PERBANDINGAN EMISI GAS BUANG ANTARA MOTOR BAHAN BAKAR EMPAT TAK BERBAHAN BAKAR PREMIUM, PERTALITE, DAN PERTAMAX - Syah budin; Rofiq Sunaryanto; Charles Situmorang (FT-USNI, 2020)
This study aims to determine the differences in carbon monoxide (CO) and hydrocarbon (HC) exhaustemissions on Honda Revo EFI system motorcycles using premium, pertalite and pertamax fuels. Thelocation of the study was conducted at PT Unilab Perdana, South Jakarta. Quantitative method withexplanatory format the results of the study showed that: The average test results obtained showed thatthe exhaust emissions released in the use of pertamax fuel (CO was 2.53%, and HC was 749 ppm). Theuse of pertalite fuel (CO is 2.62%, and HC is 837 ppm). The use of premium fuel (CO of 2.77%, andHC of 1233 ppm). Thus, within the permissible threshold of LH Decree No. 05 of 2006, namely for 4.5%CO gas and 2000 ppm HC gas with the test method at idle speed (normal engine rotation position whennot pressed by the gas). Chi square test calculation results show that, X2 count (18.95) > X2 table(5.591), so H0 is rejected. This means that there are differences in the proportions in the premium fuelgroup, pertalite and pertamax to the exhaust emissions of CO and HC. Thus, the proposed researchhypothesis has been answered, namely that there are differences in carbon monoxide (CO) and hydrocarbon (HC) exhaust emissions on Honda Revo EFI system motorcycles using premium, pertalite andpertamax fuels.